RESULTS OF RESEARCH ON BUTT JOINTS OF Q345B STEEL USING AUTOMATIC SUBMERGED ARC WELDING - Hưởng, Nguyễn; Tuan, Tong (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
Applied research of automatic submerged arc welding for welding specific materials has real and scientific importance. Experimental implementation of the welding process of Q345B high-strength low-alloy steel with square groove butt joints presented suitable welded parameters for further study. In this study, the parameters for the welding process were obtained from investigating documents and preliminary experiments. Through the initial survey, some parameters were fixed and welding processes were carried out with input elements, and then the output parameters were evaluated to identify the essential parameters of the welding processes with a 419.5 A welding current and a 16 m/h welding speed. Based on the parameters from the experiments, calculations were performed to determine the welding processes with concrete specimens. Several essential evaluative methods were utilized to evaluate the welded quality such as the tensile test, macrostructure test, and microstructure test. In addition, initial results from the application of the automatic submerged arc welding for an equivalent sample of the machine part were presented.